Characterisation of Biosurfactant Produced by Hydrocarbon-Degrading Bacteria Resistant to Cadmium - Tey, Kha Kien (2016)
Biosurfactant produced from bacteria is an alternative approach to bioremediate crude oil contaminated site which often contained heavy metal. However, there are limited studies about the production of biosurfactant in the presence of both hydrocarbon and heavy metal. Hence, the objective of this experiment was to study the effect of Cadmium (Cd) on biosurfactant production by bacteria exposed to crude oil hydrocarbon; and to characterise the biosurfactant in order to better understand its function when bacterial cells are exposed to crude oil and Cd. Three bacteria isolates (A, B and C) with known crude oil degradation activity were subjected to Cd toxicity test at 0.1 mg/L. Isolate A showed the highest growth (p<0.05) in the presence of Cd, thus most resistant to Cd, among the three tested isolates. Gram staining result showed that isolate A was Gram positive. The bacterial cells gave a positive absorbance reading of 0.99 ± 0.243 at OD625 nm for methylene blue assay and 58.4% of cell adherence to crude oil in Bacterial Adhesion to Hydrocarbons (BATH) assay, suggesting hydrophobic cell surfaces due to potential secretion of biosurfactant. Biosurfactant production by isolate A in Bushnell-Haas media using crude oil as sole carbon source exposed to 0.1 mg/L Cd showed significant increased (p<0.05) of 29.6% biosurfactant mass in dry weight compared to the control without Cd. Based on the Emulsifying Index (E24) study, the biosurfactant was able to formed the highest (p<0.05) emulsion layer with benzene (35.8 ± 1.43%) followed by both hexane (5.0 ± 0.0%) and crude oil (8.3 ± 3.36%), at room temperature, thus showing good emulsion activities. However, the isolated biosurfactant was not thermal stable as it did not retained the hydrocarbon-emulsifying activity when exposed to temperature above 60˚C. The isolated biosurfactant tested positive for the presence of sugar moiety using Dubois assay, with absorbance reading of 0.44 ± 0.032 at OD490 nm, but negative for protein using Biuret test. This suggested the biosurfactant produced by isolate A is from the glycolipid family. The presence of Cd significantly increased the secretion of biosurfactant suggested that isolate A employed the mechanism of biosynthesizing and secreting glycolipid biosurfactant to counter the toxicity due to Cd.